Synthesis and analytical applications of photoluminescent carbon nanosheet by exfoliation of graphite oxide without purification - Kaviyarasu, K.; Manikandan, E.; Kennedy, J.; Maaza, M. (Journal of materials science. Materials in electronics, 2016)
We report synthesis and structural, chemical and optical properties of graphene nanosheet prepared by facile method. The surface morphology of the graphene nanosheet was revealed using AFM studies. Raman fingerprints for single-bilayer, and few-layer graphene reflect changes in the electronic structure and electron–phonon interactions and allow unambiguous, high throughput, identification of graphene layers. Strong blue shifts were absorbed in the PL spectra that attributed to the quantum confinement effect. FTIR and, XPS results confirm the formation of carbon sheets. The topological features, structural, optical properties of single sheet were closely match with predictions of first principles atomistic modeling. Furthermore facile method of material synthesis described in this article can be used to fabricate innovative 2D nanocrystalline materials with unique properties for broad range of applications.